THE NATURE OF TRANSLATION (CASE STUDY ON TRANSLATING COMPUTER TEXT) - Nur'afifah Hasbi Nasution (Universitas Potensi Utama, 2018)
Translation is dealing with transferring meaning from source language into target language. In simple cases, it can be translating word by word. While for some cases, such translation may seem awkward or even confusing and funny. It may happen when certain words are translated into inappropriate equivalent words. The translation, then, fails to transfer the meaning from source language. Based on the aim, it is necessary to catch the idea of the text. English as the language of science, including computer, is used widely in many textbooks. In fact, there are many words which have no equivalent words in Indonesian. This study analyzes the process of translating English into Indonesian on computer text. The object of the study is English articles used by Faculty of Engineering and Computer Science of Potensi Utama University. The study shows that there are two things to be paid attention in translating English computer text into Indonesian; finding the appropriate equivalent words, and keeping non-equivalent words as they are.